ANALYSIS OF COMPANY SIZE, FINANCIAL LEVERAGE, AND PROFITABILITY AND ITS EFFECT TO CSR DISCLOSURE - Riantani, Suskim; Nurzamzam, Hafidz (Jurnal Dinamika Manajemen, 2015)
This study aims to analyze and recognize the effect of financial performance measured through company size, financial leverage and profitability to Corporate Social Responsibility Disclosure (CSRD). The research was done in Tobacco Company listed in Indonesia Stock Exchange during period of 2007-2011. Descriptive analysis and verification method was used as the research method. The purposive sampling method was used to obtain the sample and there are three cigarette companies as the sample. Multiple linear regression and correlation analysis using t test and F test were applied as a technique of analysis. The test of the classical assumption such as the normality, multicollinearity, heteroscedasticity, and autocorrelation applied before the multiple linear regression. The result shows that the company size had positive and significant effect to the CSR disclosure, financial leverage does not show significant effect to the CSR disclosure, profitability does not have significant effect to the CSR disclosure during the investigation.